A smile of joy with Adam’s chair - UMP, PNC (2018)
Pekan, September 6 - A smile of joy lit up Adam’s face after receiving Adam’s Chair, a custom made wheelchair named after him, specially designed by a group of undergraduates and lecturers from Faculty of Mechanical Engineering. Adam, a year two students at Sekolah Kebangsaan Serandu was diagnosed with Cerebral Palsy at birth, which caused impaired movement associated with abnormal reflexes, floppiness or rigidity of the limbs and trunk, abnormal posture, involuntary movements, unsteady walking, or some combination of these.